Identification of the information gap in residential energy efficiency: How information asymmetry can be mitigated to induce energy efficiency renovations - Matthew Collins; John A. Curtis (The Economic and Social Research Institute (ESRI), 2017)
Improving the energy efficiency of residential dwellings is seen by policy-makers as an important contributor to the mitigation of climate change, a topic of ever increasing interest. Many countries have put in place policies aimed at stimulating the adoption of energy efficiency retrofit measures in private households. These policies generally focus on reducing costs to home owners, which in turn increases the net benefit of retrofitting, making a retrofit more attractive. We examine the drivers of retrofitting from an information point of view, looking mainly at how expected gross benefits can be increased as a means of inducing retrofitting activities. Using survey data, we examine how perceived effects of retrofitting impact on the likelihood that a home owner possesses an expressed interest in engaging in certain retrofit measures. We find the existence of information asymmetries in many cases between those who have and have not engaged in retrofit measures, while asymmetries are present in almost all instances between those who possess an expressed interest in retrofitting and those who do not. The most effective information that can be used to bridge this asymmetry and could lead to a greater interest in retrofitting among home owners are centred around energy costs and comfort. Perceived impacts of retrofitting on occupant health, property value and mould growth are not found to be significant drivers of interest in retrofitting.
Keywords: D12; D38; Q48; 330; energy efficiency retrofitting; information asymmetry; household behaviour